Cultural policies: safeguarding and socialization of cultural heritage : (intangible and movable) (Research Announcements "Heritage BG", 2025)
Noting the presence of specifics in both parts of the heritage and their patterns – artifacts and elements recognized as valuable, the text is focuses on the efforts of society to safeguard, preserve them and transfer to the future. Regarding the movable heritage, attention is paid to its connection with the institution of the Museum. Attention is paid to the connection conservation-sustainable development socialization. National and international normative documents dedicated to this issue are indicated. References:Santova 2010: Santova, Mila. Pravata na choveka I nematerialnoto kulturno nasledstvo. – Balgarski folklor 2010, N 3-4, 150-159.Santova 2015: Santova, Mila. Politiki za opazvane na kulturnoto nasledstvo. – Nasledstvo I kulturen peizaj. Izvestia na regionalen istoricheski muzei Ruse, t. XVIII, Ruse, 135-148.Santova 2018: Santova, Mila. Prikanva sekretariata… opazvane na nematerialnoto kulturno nasledstvo dnes: sinergii, harmonii, ustoichivo razvitie. – In: Preservation of cultural heritage. Ideas and practices. Prof. Marin Drinov Publishing House of the Bulgarian Academy of Sciences. Sofia, 2018, 21-30.
Keywords: Cultural heritage; protection; sustainable development; socialization